Community of juvenile hard corals (Scleractinia) in different geomorphological type and reef benthic communities. Issue 1 (1st June 2022) - Abrar, M; Hadi, T A; Handayani, T; Zamani, N P; Suharsono,; Bengen, D G
Abstract: Juvenile corals are an important stage in the life history and demographics of coral populations in nature however, their survival is influenced by the physical environment and benthic coral reef communities. The study of juvenile coral communities with a maximum size of 10 cm on the reefs of Pulau Weh, Sabang, Aceh was conducted to observe juvenile coral communities and determine their relationship with geomorphological types and benthic reefs communities. A total of 9 sites with 72 sampling squares were distributed in different geomorphological; tectonic type with hard substrates of lava and limestone, volcanic type with predominantly sand substrate, and dead coral with algae with the presence of hot springs in the vicinity. In total, we found 25 genera of juvenile corals from 12 families, and the abundance reached 449 colonies with an average of 37.41 colonies per site. The mean density was 6.66 ± 5.99 colonies/m2 (±SD) and varied significantly between sites (p=4.878-7; <0.05), which was dominated by the genera Porites, Pavona, Acropora, Montipora, and Favia. Live coral cover (HC), dead coral algae (DCA), and hard rock substrate (RK) did not affect, however rubble coral (R) was significantly affected (p=1.9-2; <0.05). Geomorphological conditions and benthic reef cover did not show a significant effect (p = 0.48; < 0.05), although juvenile corals were very common and better in the tectonic type than the volcanic type. The survival of juvenile corals was low, where the smaller size was significantly high compared to the larger size (p=4.5-5; <0.05). Our study provides up-to-date information and data on juvenile coral communities based on geomorphological conditions and local benthic reef communities.